2016
DOI: 10.1016/j.engstruct.2015.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Performance-based seismic design of flexible-base multi-storey buildings considering soil–structure interaction

Abstract: The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. AbstractA comprehensive parametric study has been carried out to investigate the seismic performance of multi-storey shear buildings considering soil-structure interaction (SSI). More than 40,000 SDOF and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 29 publications
2
26
0
1
Order By: Relevance
“…In this investigation, steel building frames are modeled on the basis of the concept of FEMA‐440 for parametric study, which permits researchers to model special complex building structures as shear‐type buildings, representing multistory buildings having so‐called shear beams or those with relatively stiff diaphragms when compared with columns. In spite of some shortcomings, shear‐building models have been frequently utilized to evaluate the seismic behavior of multistory structures due to their simple forms and low computational efforts enabling a various ranges of parametric studies . In the steel shear‐building structures, beam‐column joints are modeled by bilinear elastic–plastic springs with 3% post‐yield strain hardening as representative of the story lateral stiffness.…”
Section: Building Prototype and Earthquake Ground Motionsmentioning
confidence: 99%
“…In this investigation, steel building frames are modeled on the basis of the concept of FEMA‐440 for parametric study, which permits researchers to model special complex building structures as shear‐type buildings, representing multistory buildings having so‐called shear beams or those with relatively stiff diaphragms when compared with columns. In spite of some shortcomings, shear‐building models have been frequently utilized to evaluate the seismic behavior of multistory structures due to their simple forms and low computational efforts enabling a various ranges of parametric studies . In the steel shear‐building structures, beam‐column joints are modeled by bilinear elastic–plastic springs with 3% post‐yield strain hardening as representative of the story lateral stiffness.…”
Section: Building Prototype and Earthquake Ground Motionsmentioning
confidence: 99%
“…The mass moment of inertia M θ and M φ (in the rotational degree-of-freedom φ) are used to account for soil incompressibility and frequency-dependency in the rocking degree-of-freedom θ; u ssi is the displacement of the structural mass relative to the ground, while u h is the foundation swaying displacement relative to the ground. The equations of motion for the SSI model and EFSDOF oscillators were solved in the time domain using the methods presented in Lu et al (2016). A suite of 20 ground motions recorded on soft soil deposits were employed in the study, as listed in Table 1.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…This simplified SSI model enables the frequency-dependent global behaviour of the soil-foundation system (i.e., foundation swaying and rocking motions) to be solved in the time domain. The adequacy of this SSI model to predict the seismic performance of nonlinear systems on soft soil was investigated by Lu et al (2016).…”
Section: Ssi Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that a 0 generally varies from zero for fixed-base buildings, to a value of three for buildings located on very soft soil deposits (Lu et al, 2016).…”
Section: Ssi Modelmentioning
confidence: 99%